Snakebite incidence and healthcare-seeking behaviors in Eastern Province, Rwanda: A cross-sectional study. - Dieudonne Hakizimana; Lauren E MacDonald; Happy Tahirih Kampire; Mihigo Bonaventure; Mahlet Tadesse; Elijah Murara; Leila Dusabe; Leandre Ishema; Janna M Schurer (Public Library of Science (PLoS), 2024)
Background Snakebite envenoming (SBE) is a potentially life-threatening event that can lead to severe physical, mental, and economic hardships, particularly in under-resourced regions like sub-Saharan Africa. In Rwanda, there have been no epidemiological assessments of SBE to guide the Ministry of Health in its efforts to reduce the burden. This study had two main objectives: first, to estimate the incidence of snakebites across districts, and second, to describe formal versus informal healthcare seeking behaviors among snakebite victims in Eastern Province, Rwanda in 2020. Methodology This cross-sectional study utilized a cluster sampling approach, involving Community Health Workers (CHWs) who recorded snakebite cases across seven districts. The descriptive analysis considered sampling weights, and healthcare seeking behavior was assessed based on the type of care sought as the first point of treatment. Findings The study surveyed 390,546 individuals across 763 villages and estimated a provincial annual incidence rate of 4.3 cases per 1,000 individuals. Incidence estimates ranged from 1.1 cases per 1,000 in Nyagatare to 9.1 cases per 1,000 individuals in Bugesera and Ngoma districts. Among the 2,545 cases recorded by CHWs, three resulted in deaths. Regarding healthcare-seeking behavior, 13% of snakebite victims (143 out of 1,098) initially consulted formal care providers (CHWs, health post/center, or hospital), while 87% sought informal care (family/friends, pharmacist, or traditional healer). Approximately half of the victims (583, 53.1%) reported severe symptoms. Unsafe practices included skin cutting/burning, tourniquet application, use of black stones, and venom extraction; only 24 cases (2.2%) received anti-venom. Conclusions This large-scale community-based assessment highlights variations in snakebite incidence between districts and confirms frequent involvement of traditional healers in management. Improving access to anti-venom and community education on the risks of ineffective practices, along with timely use of formal healthcare, are crucial. Collaboration between healthcare providers, traditional healers, community leaders, and policymakers is essential to implement targeted interventions for enhancing snakebite prevention and management strategies.